Approaches to Assessing and Monitoring of the Budget Potential Use in the Far North - Tatyana I. Barasheva (Арктика и Север, 2022)
In the current crisis conditions, improving the financial security of the territories as a factor of development and investment attractiveness of the regions is a key task. An important role in its solution is played by assessment of the budget potential, which allows creating the information basis for the development of recommendations on the mobilization of financial resources and their effective use. It has defined the goal of this article: substantiation of the methodological approach to assessing the level of budgetary potential use. It has been determined, that an increase of budget potential can be influenced by the activity of regional authorities in the course of implementation of the budget process. Within the developed meth-odological approach to evaluation of the budget potential, based on application of the integral and matrix approaches, selection of indicators is substantiated with the allocation of two groups characterizing financial security of the regions and quality of the budget process governance. In the course of the methodology approbation on the basis of data from the Far North (FN) regions, the calculations of the total integral index, assessing the level of use of budgetary potential in the regions, and its components — individual integral indices — were carried out. The FN regions are leveled by the budget potential use. Matrices grouping the regions on the level of financial security and governance quality are formed. The comparison of typological groupings and analysis of coefficients included in calculation of the integral index made it possible to study the tendencies, to reveal the specificities and problems of forming and using the budget potential in region of the Far North. It is found out that the FN regions with high and moderate levels of the budget potential use are characterized mainly by governance problems. In the regions with reduced or low level of the budget potential use, the financial problems are amplified along with managerial problems. The problem areas identified in the course of the study are a guideline for development of measures aimed at effective governance of the budget potential.